Transplant artery thrombosis and outcomes - Sugi, Mark D.; Albadawi, Hassan; Knuttinen, Grace; Naidu, Sailendra G.; Mathur, Amit K.; Moss, Adyr A.; Oklu, Rahmi (Cardiovascular Diagnosis and Therapy, 2017)
Post-transplantation allograft arterial thrombosis is a well-recognized complication associated with solid organ transplantation. Much of the literature is centered on liver and kidney transplantation, which will therefore serve as the principle basis for this review, with a brief discussion on pancreas transplantation and associated arterial complications. The number of solid organ transplants has been steadily increasing over the past decade in parallel with growing demand for organs and expansion of the transplantation criteria for both donors and recipients. This increase has been accompanied by a number of innovative medical advances and surgical techniques, as well as improved imaging that has allowed for thoughtful exploration of vascular anatomic variants and the possibilities for transplant with which they are associated. It has also been accompanied by a growing field of behavioral research, as potential recipients must weigh the risk of accepting certain organs based on perceived outcomes that may differ according to the quality of the underlying organ. Improvements in imaging technology have brought greater sensitivity to detecting arterial complications in post-operative surveillance examinations and have allowed for further development of tailored endovascular and surgical interventions for transplant-associated vascular complications. This review will focus on post-transplantation solid organ allograft artery thrombosis, including discussion of risk factors, diagnostic imaging, natural history, and therapeutic options.